Do Perceived Insider Status Influence Intent to Stay Among Nurses: The Mediating Role of Psychological Ownership - Ebele E. Nnadozie; Obinna O. Ike; Leonard I. Ugwu (SAGE Open)
Intent to stay is a phenomenon that has remained one of the recipes for an efficient and vibrant organization, which is pivotal to organizational success and continuity in Nigerian organizations. However, more knowledge of the influencing factors and mechanisms must be gained. Based on the theory of planned behavior, this present study, adopting a two-wave design, conducted a cross-sectional survey of 515 nurses of federal government-owned hospitals in Southeast Nigeria to investigate the mediating role of psychological ownership (PO) in the relationship between perceived insider status (PIS) and intent to stay (ITS) using convenience sampling. The results revealed that PIS and PO had a significant positive relationship with intent to stay. In addition, PO significantly mediated the relationship between perceived insider status and intent to stay. The study findings highlight that enhancing perceived insider status and fostering psychological ownership are critical strategies for improving nurse retention. Healthcare organizations prioritizing these factors will likely see increased job satisfaction, reduced turnover, and better patient care outcomes. Organizations can create a more stable and committed nursing workforce by understanding and addressing nurses’ psychological and emotional needs.